LOCOMOTION AND MOVEMENTS IN A FEW COLONIAL ROTIFERS OF THE ORDER FLOSCULARIACEA - BHARDWAJ, S. C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
The paper deals with the locomotion of the free-swimming colonial rotifer forms namely Lacinularia elliptica. Shephard, Sinantherina semibulata Thorpe and S. spinosa Thorpe. It also describes how the free-swimming stages (founding colonies) of fixed colonial forms move and later settle down at a suitable place The individual animals of fixed colonial forms namely L. flosculosa Muller and S. procera Thorpe also show movements of body parts. Although there is no organic connection between the individuals of a colony, yet they exhibit a good deal of coordination amongst themselves in their movements. The larvae of the various types of colonies exhibit the same type of locomotary habits.